Literature study: Diversity level of coastal echinoidea as a source of biology learning materials for biodiversity - AlFazali, Muhamad Fahad; Hanafi, Yahya; Ma’rifah, Destri Ratna (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
The diverse learning resources around students' lives have not been optimally utilized in learning. Learning resources are one of the important things in improving the learning process, the surrounding environment can be used as an effective and efficient learning resource because it provides a hands-on experience to students. Learning activities that utilize the environment either directly or not are biodiversity materials. Learning resources from the surrounding environment are also expected to make students more sensitive and easy to understand lessons. This study aims to determine the level of diversity of Echinoidea in the intertidal zone and analyze the needs of learning resources. The research method uses a literature study by searching for eight relevant articles related to the level of diversity of Echinoidea in the coastal intertidal zone on several accredited science journal websites as a source of study and then reviewing and analyzing the requirements as a source of biology learning. This study uses a narrative review design with the research instrument, namely the researcher himself. The data analysis technique used descriptive analysis. The results of the literature study showed that the diversity index of Echinoidea had a moderate diversity index. The results of the analysis of potential needs for learning resources that have been carried out show the results of research on Echinoidea diversity meet the requirements as a source of study material for high school biological diversity.